Christian Filipino Society Approaching the 21st Century - Hart, Donn V. (Silliman Journal, 2024)
At the beginning of the 20th century Philippine anthropology was “characterized by a nearly exclusive concern for two primary interests, culture history and non-Christians, especially the so-called “tribal peoples , . . The most dramatic change (since 1940). , .has been the trend toward studies of lowland rural communities.” This article summarizes, from an anthropological point of view, the known cultural contours of contemporary Filipino society.